Particle size determines effects of lipoprotein lipase on the catabolism of n-3 triglyceride-rich particles. Issue 4 (August 2015) - Xia, Lulu; Fan, Chaonan; Dong, Hua; Wang, Cui; Lu, Yuanyuan; Deckelbaum, Richard J.; Qi, Kemin
Summary Background & aims The catabolic pathways of n-3 triglyceride (TG) rich particles (n-3 TGRP) have not been clearly elucidated. In this study, we investigated the effects of lipoprotein lipase (LPL) on the catabolism of n-3 TGRP compared to n-6 TGRP in vivo and in vitro, and we determined whether particle size affects the biological functions of LPL in n-3 TGRP catabolism. Methods Four types of lipid emulsions, chylomicron (CM)-sized n-3 TG and n-6 TG emulsions, and very low density lipoprotein (VLDL)-sized n-3 TG and n-6 TG emulsions, were labeled with 1, 1′-dioctadecy1-3, 3, 3′, 3′-tetramethylindo-carbocyanine perchlorate (DiI) and administered via a bolus injection to LPL gene knockout (LPL+/−) mice in vivo and were added to cultured LPL miRNA-transfected 3T3-L1 adipocytes in vitro. Results With CM-sized emulsions, a reduction in LPL expression in LPL+/− mice had almost no effect on tissue uptake of n-3 TG emulsions with smaller changes in their initial blood clearance; however, greater effects were observed for VLDL-sized n-3 TG emulsions with respect to tissue uptake with greater changes in their initial blood clearance, compared to n-6 TG emulsions with the same size. In vitro, LPL miRNA transfection had smaller effects on CM-sized and greater effects on VLDL-sized n-3 TG emulsions, with respect to particle uptake, cell TG mass, particle-cell binding and particle lipolysis. Conclusion These results suggested that LPL is more important for catabolism of n-3 TGRP of smaller size; whereas it is essential for catabolism of all sizes of n-6 TGRP.